The narrative elements and dominant structural components in Iraqi prose poetry. - Salim, Prof Dr. Haitham Abbas; Mashat, Zahra Jamil (Thi Qar Arts Journal, 2023)
The importance of narration as a literary field that has received widespread attention from writers and critics in their various writings, whether at the level of theorization or practice. This is due to its importance as a discourse accompanying human life in various societies and at all times and places. The features of narration have varied and its manifestations have multiplied, as it represents the way of storytelling in expressive forms, whether written or spoken. However, this concept has evolved over time to become a theory in itself, like other literary theories. Narration enters into various aspects of life to the extent that we can say that everything in existence is a narrative even if it includes only one element of narration. The modern poetic text (prose poem) has opened up to the use of various techniques to create a poetic aesthetic that attracts the reader’s attention and stops them. As a result of freedom and rejection of the rules and principles commonly accepted in poetry for decades, poets of the prose poem have opened up to other arts in order to elevate the poetic text aesthetically and artistically, especially after they abandoned the external rhythm (metrical) commonly accepted. This is what prompted them to search for new poetic areas, as they found their quest for poetic renewal lies in prose with its various manifestations, especially the narrative aspect in structure and performance. This is supported by the term “prose poem” itself, which is composed of two parts, which proves the employment of the narrative aspect, especially with its main compositional elements, namely event, character, and plot; because their presence in the selected poetic models in our research records a clear dominance over the structure and performance of the prose poem.